PENGARUH FINANCIAL TARGET, INEFFECTIVE MONITORING, DAN TOTAL ACCRUALTERHADAP FINANCIAL DISTRESS PADA BANK UMUM SYARIAH YANG TERDAFTAR DI OTORITAS JASA KEUANGAN TAHUN 2018 – 2022 - Febry Anggraeni Septariani; Santi Susanti; Susi Indriani (Jurnal Ilmiah Manajemen dan Akuntansi, 2024)
This study aimed to examine the effect of Financial target (ROA), Ineffective monitoring (IND) and Total accrual (TATA) on Financial distress. The research method used in this research is a quantitative method. Data collection techniques are carried out using documentation techniques. The population used in this research is Sharia Commercial Banks registered with the Financial Services Authority in 2018-2022 using a purposive sampling method, so the number of samples for this research is 60 financial report data from Sharia Commercial Banks registered with the Financial Services Authority for 5 years. Data was obtained by collecting data from the annual financial reports of Sharia Commercial Banks on each company's website. The data analysis technique used is logistic regression analysis which has previously passed the multicollinearity test, model suitability test and hypothesis testing using SPSS software for windows. The research results show that Financial target(ROA) has a significant influence on financial distress, while Ineffective monitoring (IND) and Total Accruals (TATA) do not have a significant influence on financial distress. And simultaneously Financial target (ROA), Ineffective monitoring (IND) and Total accrual (TATA) have a significant effect on financial distress in Islamic commercial banks, with a Nagelkerke R Square value of 17.8%.